Price Strategy Analysis, Marketing Public Relations, And Personal Selling Of Purchasing Decisions With Brand Awareness As A Moderation Variable - Tristi Iriana; Hery Margono (ITB AAS INDONESIA, 2023)
This study empirically tests the influence of price, marketing public relations, and personal selling on purchasing decisions with brand awareness as variable moderation. The independent variables is price, marketing, public relations, and personal selling. The dependent variable is the purchase decision, while the moderation variable is brand awareness. The sample was carried out by purposive sampling method. Data collection was carried out with questionnaires distributed directly to respondents totaling 100 customers of PT Rentokil. The statistical method uses Moderating Regression Analysis, with probably testing of statistical test t. The results of this study show that the Effect of Price on Purchasing Decisions has insignificant results, which means it has no effect. Marketing public relations on purchasing decisions, the power of personal selling on buying decisions, the power of prices, marketing public relations, and personal selling moderated by brand awareness of buying decisions have significant results and have a direct influence on dependent variables.